Utilization of Cassava into Mocaf Flour as A Processed Product by The Sumber Makmur Women Farmer Group in Tepisari Village - Umi Salamah; Nur Rokhimah Hanik; Ratna Dewi Eskundari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Cassava (Manihot esculenta crantz) is a type of tuber which has a carbohydrate content of 34% and can be processed as an alternative staple. One of which is mocaf flour (Modified Cassava Flour) which is flour derived from cassava and modified by lactic acid bacteria fermentation. Mocaf flour can be used to make bread, noodles and cakes. One of the efforts to utilize cassava into mocaf flour into processed products has been carried out by the Sumber Makmur Women Farmers Group (KWT). The purpose of this research is to improve the skills of KWT Sumber Makmur members of Tepisari Village in producing mocaf flour independently so they can create processed food products from mocaf flour that are of higher quality and variety. This research method uses a descriptive qualitative approach with the results obtained from making Mocaf Cookies which will be discussed and observed, namely swelling power, taste, aroma and texture. The results obtained from the process of making mocaf flour with tape yeast can produce good quality mocaf flour and processing mocaf cookies has produced cookies with sufficient expansion power, savory taste, distinctive aroma and crunchy texture. The use of cassava into mocaf flour at KWT Sumber Makmur, it is able to provide increased insight into the process of making mocaf flour. As well as the development of KWT mocaf cookies processed products that have high selling value.